Ideal Government and the Mixed Constitution in the Middle Ages - Blythe, James M., 1948- (Book collections on Project MUSE., 1992)
Ancient Greeks and Romans often wrote that the best form of government consists of a mixture of monarchy, aristocracy, and democracy. Political writers in the early modern period applied this idea to government in England, Venice, and Florence, and Americans used it in designing their constitution. In this history of political thought James Blythe investigates what happened to the concept of mixed constitution during the Middle Ages, when the work of the Greek historian Polybius, the source of many of the formal elements of early modern theory, was unknown in Latin. Although it is generally argued that Renaissance and early modern theories of mixed constitution derived from the revival of classical Polybian models, Blythe demonstrates the pervasiveness of such ideas in high and late medieval thought. The author traces medieval Aristotelian theories concerning the best form of government and concludes that most endorsed a limited monarchy sharing many features with the mixed constitution. He also shows that the major early modern ideas of mixed constitutionalism stemmed from medieval and Aristotelian thought, which partially explains the enthusiastic reception of Polybius in the sixteenth century. Originally published in 1992. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.